2017
DOI: 10.1111/lang.12225
|View full text |Cite
|
Sign up to set email alerts
|

Collocations in Corpus‐Based Language Learning Research: Identifying, Comparing, and Interpreting the Evidence

Abstract: This article focuses on the use of collocations in language learning research (LLR). Collocations, as units of formulaic language, are becoming prominent in our understanding of language learning and use; however, while the number of corpus‐based LLR studies of collocations is growing, there is still a need for a deeper understanding of factors that play a role in establishing that two words in a corpus can be considered to be collocates. In this article we critically review both the application of measures us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
199
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 275 publications
(230 citation statements)
references
References 47 publications
4
199
0
7
Order By: Relevance
“…Gablasova et al. () highlighted three important aspects of corpus‐based distributional information for RMCs: exclusivity, dispersion, and directionality. Exclusivity concerns the statistical significance of the lexical associations in RMCs; dispersion concerns the evenness of the RMC distribution in a corpus.…”
Section: Analyzing Phraseological Competencementioning
confidence: 99%
See 4 more Smart Citations
“…Gablasova et al. () highlighted three important aspects of corpus‐based distributional information for RMCs: exclusivity, dispersion, and directionality. Exclusivity concerns the statistical significance of the lexical associations in RMCs; dispersion concerns the evenness of the RMC distribution in a corpus.…”
Section: Analyzing Phraseological Competencementioning
confidence: 99%
“…The most intuitive metric for formulaicity is RMC frequency in a native speaker corpus. However, studies have shown that RMC frequency “may not be the best predictor of the regularity and predictability in language use” (Gablasova et al., , p. 160). Its statistical importance may be subject to the relative frequencies of the individual words in the combination (Evert, ; Gries, ).…”
Section: Distribution‐based Approach To Phraseologymentioning
confidence: 99%
See 3 more Smart Citations